Pengembangan Budaya Membaca Siswa Madrasah Ibtidaiyah di Kota Semarang - Fahrurrozi, Fahrurrozi (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2016)
This mentoring is motivated by a study, which shows the importance of reading skills of students in the early grades and determine their learning success in the next grade. On the basis of these reasons, then the reading culture is an alternative that can be developed school / madrasah. Based on that background, the mentoring was implemented to develop a reading culture of students in the madrasas built FITK UIN Walisongo, namely MIT Nurul Islam, MI Darul Ulum, MI Miftahul Akhlaqiyah. There are several assistance activities undertaken to develop a culture of reading, the Focus Group Discussion, MoU between the Department of MPI UIN Walisongo the MI side, the MoU with the Regional Library related to the addition of books, parenting about the growth of the reading culture of children, training-based learning literacy for teachers, and a comparative study to MIN Model Sleman, Yogyakarta. Pendampingan ini dilatarbelakangi oleh sebuah penelitian, yang menunjukkan pentingnya kemampuan baca siswa di kelas awal dan menentukan keberhasilan belajar mereka pada kelas selanjutnya. Atas dasar alasan itulah, maka budaya baca adalah sebuah alternatif yang dapat dikembangkan sekolah/madrasah. Berdasarkan latar belakang itulah, maka pendampingan dilaksanakan untuk mengembangkan budaya baca siswa di madrasah binaan FITK UIN Walisongo, yaitu MIT Nurul Islam, MI Darul Ulum, MI Miftahul Akhlaqiyah. Terdapat beberapa kegiatan pendampingan yang dilakukan untuk mengembangkan budaya baca, yaitu Focus Group Discussion, MoU antara Jurusan MPI UIN Walisongo dengan MI dampingan, MoU dengan Perpustakaan Daerah terkait penambahan koleksi buku, parenting tentang penumbuhan budaya baca anak, pelatihan pembelajaran berbasis literasi bagi guru, dan studi banding ke MIN Model Kabupaten Sleman Yogyakarta.